2021
DOI: 10.3390/jof7010060
|View full text |Cite
|
Sign up to set email alerts
|

Differential miRNA Expression in Human Macrophage-Like Cells Infected with Histoplasma capsulatum Yeasts Cultured in Planktonic and Biofilm Forms

Abstract: Histoplasma capsulatum affects healthy and immunocompromised individuals, sometimes causing a severe disease. This fungus has two morphotypes, the mycelial (infective) and the yeast (parasitic) phases. MicroRNAs (miRNAs) are small RNAs involved in the regulation of several cellular processes, and their differential expression has been associated with many disease states. To investigate miRNA expression in host cells during H. capsulatum infection, we studied the changes in the miRNA profiles of differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…The progression of the disease hinges on the yeast cells’ ability to survive and multiply within these phagocytic cells, making the host-pathogen interaction a highly intricate phenomenon and a critical determinant of the disease's course. In this context, the innate immune response plays a pivotal role in influencing disease progression ( Cleare et al, 2017 ; Cohen et al, 2022 ; Guimarães, de Cerqueira, et al, 2011 ; Hahn et al, 2022 ; Loose et al, 1983 ; Mittal et al, 2019 ; N. de S. Pitangui et al, 2021 ; Shankar et al, 2011 ).…”
Section: Histoplasmosis and Paracoccidioidomycosis Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The progression of the disease hinges on the yeast cells’ ability to survive and multiply within these phagocytic cells, making the host-pathogen interaction a highly intricate phenomenon and a critical determinant of the disease's course. In this context, the innate immune response plays a pivotal role in influencing disease progression ( Cleare et al, 2017 ; Cohen et al, 2022 ; Guimarães, de Cerqueira, et al, 2011 ; Hahn et al, 2022 ; Loose et al, 1983 ; Mittal et al, 2019 ; N. de S. Pitangui et al, 2021 ; Shankar et al, 2011 ).…”
Section: Histoplasmosis and Paracoccidioidomycosis Pathogenesismentioning
confidence: 99%
“…Besides these described genes in Histoplasma spp., recent publications have shown that biofilm formation could represent an important virulence mechanism in Histoplasma spp. ( Gonçalves et al, 2020 ; Pitangui et al, 2016 , 2021 ; Pitangui et al, 2012 ).…”
Section: Virulence Factors Of Histoplasma Sppmentioning
confidence: 99%
See 1 more Smart Citation